A Search for Zγ Resonances and TileCal Performance Studies in the ATLAS Experiment - Rapheeha, Ntsoko Phuti (University of the Witwatersrand, Johannesburg, 2024)
The observation of the Higgs boson by the ATLAS and CMS Collaborations at the LHC in 2012 marked a pivotal moment, completing the Standard Model, SM, of particle physics. While the SM has propelled our understanding forward with remarkable success, its brilliance is shadowed by its inability to account for several fundamental aspects of nature, such as the existence of dark matter, the mysterious origins of neutrino masses, and the glaring absence of gravity within its framework. Motivated by the discrepancies observed in multi-lepton final states at the LHC, this thesis conducts a search for high-mass spin-0 and spin-2 resonances decaying into the Zγ final state utilising the Run 2 dataset collected by the ATLAS detector at √s = 13 TeV, with an integrated luminosity of 140 fb−1. A mild excess of 2.1σ is observed at 250 GeV, a range of interest predicted by the model that accounts for the multi-lepton anomalies. Despite the localised excesses, no significant deviation relative to the SM background is observed. Upper limits, established at a 95% confidence level, are set on the production cross-section times the decay branching ratio into Zγ for high-mass resonances in the mass range of 220 GeV to 3400 GeV. These upper limits improve on Run 1 results by a factor of 1.9 to 4 in the mass range between 250 GeV and 2400 GeV. This thesis also delves into performance studies of the ATLAS Tile calorimeter, TileCal. The TileCal is a hadronic sampling calorimeter consisting of scintillating tiles that are sandwiched between steel slabs. The calibration and uniformity of the response of gap and crack scintillators in TileCal are validated by studying their response to isolated muons. The response of these scintillators to isolated muons, produced by W → µνµ decays in pp collisions during Run 2 data-taking, is compared to Monte Carlo simulations. Additionally, preliminary luminosity measurements from TileCal D cells are used to analyse drifts in the primary ATLAS luminosity measurements provided by the LUCID detector during the 2022 data taking at √s = 13.6 TeV.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2024
Keywords: Standard Model; Tile Calorimeter; Luminosity; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-4: Quality education